Measuring service contract performance : preliminary findings on effects of service complexity, managerial capacity, and paired history /: preliminary findings on effects of service complexity, managerial capacity, and paired history. (2021) - Hunter, Andrew P; Sanders, Greg, 1980-
No abstract available